Implementasi Pembelajaran Dengan Strategi Konflik Kognitif Berbantuan Aplikasi Augmented Reality Dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis Pada Siswa SMP Negeri 4 Percut Sei Tuan - Rusmini, Rusmini; Fitrah Sari Wahyuni Harahap; Doni Irawan Daragih; Adinda Dwi Arwilla; Fauziah Zahra Pane (Jurnal Pengabdian Ahmad Yani, 2024)
Mathematical problem solving is the process of solving problems or problems using concepts, principles and methods related to mathematics. Mathematical problem-solving ability is the skill to use mathematical concepts and strategies in solving real problems. Students' mathematical problem-solving abilities can increase with the implementation of learning assisted by Augmented Reality (AR). The aim of this community service is to implement learning media with AR-assisted cognitive conflict strategies. Does the implementation of this media affect students' mathematical problem-solving abilities regarding cubes and blocks. This community service was carried out at SMP Negeri 4 Percut Tuan for class VIII students, where each class took 5 people as representatives and the number of students who took part in the socialization process was 25 people. Activities are carried out in stages 1) socialization of AR-assisted learning media, 2) Implementation of AR-assisted learning media, 3) evaluation by providing a pre-test before implementation and providing a questionnaire, post-test after implementation. Based on the results of the questionnaire, the implementation of learning media with AR-assisted cognitive conflict strategies motivates students and strengthens understanding of concepts so that it has an impact on students' mathematical problem-solving abilities. The pre-test and post-test data were carried out by the N-Gain test, there was an increase and the t test showed differences between before and after implementation. This means that there is a significant influence from the implementation of learning media with AR-assisted cognitive conflict strategies on students' mathematical problem-solving abilities. Keywords: Implementation, Learning Media, Augmented Reality, Mathematical Problem Solving Ability.